Мagnetoresistive Properties of Nanodimentional Materials: Variation Measuring Currents and to Minimize Electronic Noise - S.O. Volkov; O.P. Tkach; L.V. Odnodvorets; Yu.V. Khyzhnya (Журнал нано- та електронної фізики)
The circuit and software of the electronic block for varying the magnitude of the measuring current and minimization of electronic noise in the automated laboratory complex for measuring of the magnetoresistance in nanodimentional film materials have been designed. Investigation of the magnetoresistive properties of films based on Co and Al or Cu, Fe, and Pd or Au different phase structure with a total thickness of 20 to 150 nm at different measuring currents were performed. It was established that irrespective of the phase composition of the film materials at the value of the measuring current of 100 mA and 10 from films of unstable electrical signal asymmetric shape with a maximum zero uncertain is observed. The most effective for all film samples is measuring current 10 mA, at which the signal becomes a symmetrical and stable.